The Reproductive System and Ovarian Development of the Adult Olive Psylla Euphyllurα phillyreαe Foerster (Homoptera: Aphalaridae) - Prophretou-Athanasiadou D. Α.; Tzanakakis, M.E (ENTOMOLOGIA HELLENICA, 1998)
The gross morphology of the reproductive system of adult females and males of the olive psylla Euphyllurα phillyreαe Foerster (Homoptera: Aphalaridae) is given. Five stages of ovarian development are distinguished and described, based on the size and shape of the ovaries and ovarioles, on the separation of the vitellarium from the germarium, and on the appearance and shape of oocytes.